Hubungan Permainan Digital Edukatif dengan Kreativitas Anak Usia Dini di TK Kh. Dewantoro - Sinta Abdullah; Elva M. Sumirat; Dewi Siti Fareliya Ishak; Nurfadila Agus Pakaya; Nayla Arina Mokodompit; Cahyani Citra Piliang (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
The development of digital technology has a great impact on the world of education, including early childhood learning. One of the forms of utilizing the technology is an educational digital game designed to help children's learning process in a fun and interactive way. This research aims to find out the relationship between educational digital games and early childhood creativity. The research method used is a quantitative approach with a type of correlational research. Data collection is carried out through observation of early childhood who use educational digital games in learning and playing activities. Research results show that educational digital games have a positive relationship with the development of children's creativity. Children become more active in thinking, able to develop imagination, express new ideas, and have confidence in completing the challenges given in the game. In addition, educational digital games also help improve problem-solving skills and train children's concentration. With the right guidance from teachers and parents, educational digital games can be an effective learning medium to support early childhood creativity.